Sexual rights as human rights: a guide to authoritative sources and principles for applying human rights to sexuality and sexual health. Issue 46 (November 2015) - Miller, Alice M.; Kismödi, Eszter; Cottingham, Jane; Gruskin, Sofia
Abstract: This Guide seeks to provide insight and resources to actors interested in the development of rights claims around sexuality and sexual health. After engaging with the vexed question of the scope of sexual rights, it explores the rules and principles governing the way in which human rights claims are developed and applied to sexuality and sexual health, and how that development is linked to law and made a matter of state obligation. This understanding is critical to policy and programming in sexual health and rights, as it supports calling on the relevant range of human rights, such as privacy, non-discrimination, health or other universally accepted human rights, as well as demanding the action of sta tes under their international and national law obligations to support sexual health. Résumé: Ce Guide cherche à transmettre des connaissances et des ressources aux acteurs intéressés par le développement de revendications relatives aux droits autour de la sexualité et la santé sexuelle. Après avoir abordé la question controversée de la portée des droits sexuels, il explore les règles et les principes qui gouvernent la manière dont les revendications fondées sur les droits de l'homme sont développées et appliquées à la sexualité et la santé sexuelle, et comment ce développement est lié à la législation et devient une obligation étatique. Cette compréhension est essentielle pour définir les politiques et la programmation en matière de santé et droits sexuels, car elle soutient les actions exigeant de bénéficier de tout l'éventail des droits de l'homme, comme la protection de la vie privée, la non-discrimination, la santé ou d'autres droits fondamentaux acceptés universellement, tout en demandant aux États de prendre des mesures au titre de leurs obligations juridiques nationales et internationale de soutenir la santé sexuelle. Resumen: Esta Guía tiene como objetivo brindar conocimientos y recursos a los actores interesados en la formulación de afirmaciones de derechos relacionados con la sexualidad y salud sexual. Después de abordar la controvertida cuestión del alcance de los derechos sexuales, explora las reglas y principios que rigen la manera en que las afirmaciones de derechos humanos son formuladas y aplicadas a la sexualidad y salud sexual, y cómo esa formulación está vinculada con la ley y pasa a ser cuestión de obligación del Estado. Este entendimiento es fundamental para las políticas y programación en salud y derechos sexuales, ya que apoya hacer un llamado a los diversos derechos humanos pertinentes, tales como privacidad, no discriminación, salud u otros derechos humanos aceptados universalmente, así como exigir que los Estados tomen medidas, de conformidad con sus obligaciones de derecho internacional y nacional, para apoyar la salud sexual.